Digitization at the Heidelberg University Library: the digital Bibliotheca Palatina project - Probst, Veit (Digital Philology, 2018)
The world-famous Bibliotheca Palatina holds more than 3.000 medieval manuscripts, which are today divided between the Vatican Library in Rome and the Heidelberg University Library. This article discusses the academic, technical, and organizational challenges and solutions for a digitization project that is now drawing to its close. Its goal has been to digitally reconstruct the Bibliotheca Palatina and to make it available, as one single online edition, to scholars all over the world, with new opportunities for access and research